Diversity, cover, shoot density, and distribution of seagrasses in the coastal areas of Gingoog City, Misamis Oriental, Philippines - Jhun Rheil H. Molina; Michael Jeriel I. Bersaldo (Davao Research Journal)
Seagrass is a vital part of the coastal environment because it offers refuge, food, and protection for a variety of animals. Despite its ecological and economic importance, seagrass meadows are under threat globally due to natural and human-caused activities. This study aims to establish baseline data on seagrass diversity, composition, cover, shoot density and distribution in Gingoog City, Misamis Oriental that would serve as a useful reference for future initiatives in management and conservation measures. A total of six species of seagrasses were identified in two sampling stations namely: Thalassia hemprichii, Halophila ovalis, Enhalus acoroides, Halodule pinifolia, Halodule uninervis, and Syringodium isoetifolium. These two sampling stations exhibited a mixed stand of seagrass community. The result of diversity indices showed that barangay Lunao was more diverse than barangay San Juan (H'=0.99). Shoot density and distribution of seagrass showed preferences in different regions of the seagrass beds where Thalassia hemprichii species was widely distributed and dominated in Barangay Lunao while Halodule pinifolia has some restrictions in its distribution with high shoot density in the high intertidal region of the seagrass of Barangay San Juan. This high density of seagrass especially on Halodule pinifolia in a disturbed area is important in the coastal ecosystem because it maintains the seagrass diversity, actively stabilizes sediment, improves water quality, and supports a vast number of the marine organisms in this disturbed area of the coastal water of barangay San Juan.